Keys to soil taxonomy (Virginia Polytechnic Institute and State University, 1990)
This book 'provides the taxonomic keys necessary for the classification of soils in a form that can be used easily in the field' and that it 'acquaints users of the taxonomic system with recent changes in the system' --Michael L. Golden, Director of the Soil Survey Division of the U.S. Department of Agriculture